Teacher Professionalism and the Influence of Education Level, Training, and Teaching Experience - Nurhidayah, Nurhidayah; Lian, Bukman; Wardiah, Dessy (Graduate Program Magister Manajemen Pendidikan, 2022)
This study determined the effect of the level of education, training and teaching experience partial and together on the professionalism of teachers. This research was quantitative with a survey design. This research was conducted in a high school in Zone III, Muara Enim Regency, with a 50 respondents. Data were collected using questionnaires and documentation. The validity test uses Pearson's product moment, while the reliability test uses K-R.20. The prerequisite test of data analysis used normality test, linearity test, multicollinearity test, while data analysis used multiple linear regression. The results showed that there is an effect of the level of education, training and teaching experience partial and simultaneous on the professionalism of teachers from senior high school in Zone III at Muara Enim Regency.